IFNG-mediated immune responses enhance autophagy against Mycobacterium tuberculosis antigens in patients with active tuberculosis - Rovetta, Ana Inés; Peña, Delfina; Hernández del Pino, Rodrigo Emanuel; Recalde, Gabriela María; Pellegrini, Joaquín Miguel; Bigi, Fabiana; Musella, Rosa María; Palmero, Domingo; Gutierrez, Marisa; Colombo, Maria Isabel; García, Verónica Edith (Taylor & Francis, 2019)
Protective immunity against Mycobacterium tuberculosis (Mtb) requires IFNG. Besides, IFNG-mediated induction of autophagy suppresses survival of virulent Mtb in macrophage cell lines. We investigated the contribution of autophagy to the defense against Mtb antigen (Mtb-Ag) in cells from tuberculosis patients and healthy donors (HD). Patients were classified as high responders (HR) if their T cells produced significant IFNG against Mtb-Ag; and low responders (LR) when patients showed weak or no T cell responses to Mtb-Ag. The highest autophagy levels were detected in HD cells whereas the lowest quantities were observed in LR patients. Interestingly, upon Mtb-Ag stimulation, we detected a positive correlation between IFNG and MAP1LC3B-II/LC3-II levels. Actually, blockage of Mtb-Ag-induced IFNG markedly reduced autophagy in HR patients whereas addition of limited amounts of IFNG significantly increased autophagy in LR patients. Therefore, autophagy collaborates with human immune responses against Mtb in close association with specific IFNG secreted against the pathogen.